2010
DOI: 10.1111/j.1365-2958.2010.07297.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bps polysaccharide of Bordetella pertussis promotes colonization and biofilm formation in the nose by functioning as an adhesin

Abstract: SummaryMany respiratory pathogens establish persistent infection or a carrier state in the human nasopharynx without overt disease symptoms but the presence of these in the lungs usually results in disease. Although the anatomy and microenvironments between nasopharynx and lungs are different, a virulence factor with an organ-specific function in the colonization of the nasopharynx is unknown. In contrast to the severity of pertussis and mortality in non-vaccinated young children, Bordetella pertussis results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
170
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(184 citation statements)
references
References 60 publications
10
170
2
2
Order By: Relevance
“…We have shown that both B. bronchiseptica and B. pertussis are capable of forming biofilms in the upper respiratory tract of infected animals (13,14,53). These findings, combined with the presence of clusters, microcolonies, and tangles of B. bronchiseptica and B. pertussis bacteria in explant tissues and nasal biopsy specimens of patients, strengthen the hypothesis that Bordetella bacteria utilize biofilms as a means to persist and circulate between their mammalian hosts (22,47,54).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…We have shown that both B. bronchiseptica and B. pertussis are capable of forming biofilms in the upper respiratory tract of infected animals (13,14,53). These findings, combined with the presence of clusters, microcolonies, and tangles of B. bronchiseptica and B. pertussis bacteria in explant tissues and nasal biopsy specimens of patients, strengthen the hypothesis that Bordetella bacteria utilize biofilms as a means to persist and circulate between their mammalian hosts (22,47,54).…”
supporting
confidence: 64%
“…We have previously shown that bpsA-D is not required for the early steps of biofilm formation, in particular, the initial attachment to abiotic surfaces (14,48). Instead, Bps is required at a step postattachment and contributes to the formation of the complex architecture of Bordetella biofilms (14,48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of medically important biofilm-forming bacteria produce partially de-N-acetylated poly-␤-1,6-N-acetyl-D-glucosamine (dPNAG) 5 exopolysaccharides, also referred to as polysaccharide intercellular adhesin. dPNAG was first described in Staphylococcus epidermidis (8) but has now been determined to be a component of the biofilm matrices of Staphylococcus aureus (9), Escherichia coli (10), Acinetobacter baumannii (11), Bordetella bronchiseptica (12), Bordetella pertussis (13), Actinobacillus pleuropneumoniae (14), Yersinia pestis (15), and Burkholderia species (16).…”
mentioning
confidence: 99%
“…Poly-␤-1,6-N-acetyl-D-glucosamine, variously referred to as PGA, PNAG, PIA, or Bps, is a secreted polymer that mediates cell-cell and cell-abiotic-surface interactions that stabilize biofilms of diverse bacterial species (1,10,16,23,31,34,48,49,62). This polysaccharide also promotes adherence to plant surfaces (41) and colonization of the mammalian respiratory tract (17) and is expressed by pathogenic Escherichia coli during mammalian infections (13). Genes of the E. coli pgaABCD operon are required for polymerization (pgaC, pgaD), partial N-deacetylation (pgaB), and secretion (pgaA, pgaB) of PGA (32).…”
mentioning
confidence: 99%